Transformasi Wilayah Jember : Menyatukan Potensi, Mewujudkan Perubahan - Ayu Sukma Wardhani; Erlin Kurniati (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
Jember Regency is one of the strategic regions in East Java with significant potential in agriculture, tourism, and education. However, challenges such as development inequality, infrastructure gaps, and underutilized local resources remain major obstacles. This article explores the transformation of the Jember region through an integrated approach involving community participation, sustainable spatial planning, and the strengthening of local economic sectors. The objective is to unify scattered potentials into a collective force that drives inclusive and sustainable development. By identifying key challenges and strategic opportunities, this article offers policy recommendations and implementation steps to realize tangible changes in the Jember region. Regional transformation does not only focus on physical aspects, but also emphasizes the development of human resources and strengthening local institutions. Innovation in the management of the agricultural sector, the development of tourist destinations based on local wisdom, and improving the quality of education are important pillars in the regional development strategy. A collaborative approach between the government, private sector, academics, and the community is expected to create synergy that encourages equitable economic growth. Through the integration of cross-sector policies and a data-based approach, the development of the Jember region can be directed towards a transformation that is equitable, adaptive, and sustainable. Policies are needed that are not only reactive, but also proactive, in responding to global dynamics and local needs. The implementation of appropriate technology and the digitalization of public services are also important parts in increasing the efficiency and affordability of development.